Making Public Pasts: The Contested Terrain of Montreal's Public Memories, 1891-1930 - Cupido, Robert (Labour / Le Travail, 2005)
The article reviews the book, "Making Public Pasts: The Contested Terrain of Montreal's Public Memories, 1891-1930," by Alan Gordon.